1997
DOI: 10.1289/ehp.971051334
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lead intakes for mother/child pairs and relevance to pharmacokinetic models.

Abstract: Blood and environmental samples, including a quarterly 6-day duplicate diet, for nine mother/child pairs between the mothers and their children i overall contribution of tissue lead to blood lead. Results from this study sugst that fractioxia absorption of ingested lead by child 6-11 years of age is cmpable with absorption patterns observed among adult females in the 29-37-year-old age rang. Because p kinetic models apply a 40-50% absorpion even for 7-year-old children, firther iniions on fractional absotpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 38 publications
1
25
0
1
Order By: Relevance
“…The variations observed in both isotopic composition and BPb concentration for premenopausal and postmenopausal subjects in the study compared with the smooth trends found in nonpregnant adult females 18-35 years of age (37) (Figures 4 and 5) are considered to reflect more extensive bone remodeling in the older subjects and larger fluctuations in BPb concentration in particular. The significant relations between total lead in blood and initial BPb concentration observed for the elderly subjects ( Figure 8) compared with the scatter for pregnant subjects was, however, unexpected and at this stage cannot be easily explained.…”
Section: Discussionmentioning
confidence: 67%
“…The variations observed in both isotopic composition and BPb concentration for premenopausal and postmenopausal subjects in the study compared with the smooth trends found in nonpregnant adult females 18-35 years of age (37) (Figures 4 and 5) are considered to reflect more extensive bone remodeling in the older subjects and larger fluctuations in BPb concentration in particular. The significant relations between total lead in blood and initial BPb concentration observed for the elderly subjects ( Figure 8) compared with the scatter for pregnant subjects was, however, unexpected and at this stage cannot be easily explained.…”
Section: Discussionmentioning
confidence: 67%
“…In other words, lead in the bloodstream may also be composed of lead that has been remobilized from endogenous sources, such as the skeleton, that have accumulated lead over medium to long periods of exposure (e.g., > 6 months). The importance of mobilized skeletal lead as a contributor to blood lead levels has been shown in adults (21,(47)(48)(49)(50), and in children (51). As a result of the mixing of lead from these different exogenous and endogenous sources, there may be a shift in the blood isotopic ratios away from the isotopic ratios of the main exogenous source(s) of exposure toward the isotopic values of lead released from the endogenous (skeletal) source(s).…”
Section: Discussionmentioning
confidence: 99%
“…If the acute oral reference dose was not given, the chronic oral reference dose was used. Oral reference doses were converted to intravenous doses based on a conservative assumption that only 10% of a gastrointestinal dose of heavy metal would be absorbed with the exception of Hg [52][53][54]. Thus, an "intravenous reference dose" would be 1/10 th of the oral reference dose.…”
Section: Calculations Of Estimated Tolerable Acute Intravenous Dosementioning
confidence: 99%